2009
DOI: 10.1159/000261502
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Fasciitis of the Breast Previously Misdiagnosed as Breast Carcinoma

Abstract: Background: Nodular fasciitis of the breast is a rare be-nign pathology that can mimic breast cancer clinically, radiologically, and histopathologically. Case Report: An 18-year-old female patient had first visited a physician in a different center with the complaint of a lump in her left breast. Breast examination had revealed a palpable mass located in the left upper outer quadrant. Ultrasonography had demonstrated a hypo-echoic lesion. Excisional biopsy of the lump had been performed and histopathologic exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Several case reports describe nodular fasciitis with clinical presentations, imaging studies, and fine-needle aspiration cytology mimicking malignancy leading to misdiagnosis of breast cancer, sarcoma, and pleomorphic adenoma [7][8][9][10]. Although the pathogenesis eludes current knowledge, proposed mechanisms include response to traumatic injury or other reactive and inflammatory processes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports describe nodular fasciitis with clinical presentations, imaging studies, and fine-needle aspiration cytology mimicking malignancy leading to misdiagnosis of breast cancer, sarcoma, and pleomorphic adenoma [7][8][9][10]. Although the pathogenesis eludes current knowledge, proposed mechanisms include response to traumatic injury or other reactive and inflammatory processes [7].…”
Section: Discussionmentioning
confidence: 99%
“…There is mito c ac va on, with no atypical cells. Immunohistochemical examina on shows that spindle cells express vimen n and ac n, but not desmin, kera n or S-100 proteins 5,7 . Rapid onset, chronic infl amma on in the stroma, and the absence of atypia suggests that the lesion is benign 8 .…”
mentioning
confidence: 99%
“…The case has been followed up for the past 30 months and there has been no evidence of recurrence. such as high cellularity, increased mito c ac vity, and infi ltra ve growth pa ern 7 . Ozben et al 7 reported a case of NF of the breast previously misdiagnosed as breast carcinoma.…”
mentioning
confidence: 99%
See 2 more Smart Citations